Analisis Materi dan Soal Matematika dalam Buku Tematik Kurikulum 2013 Siswa Sekolah Dasar Kelas V Berdasarkan Taksonomi TIMSS - Wahyuningrum, Hesty, Prof. Dr. Budi Murtiyasa, M. Kom (2017)
The low mathematics achievement of Indonesian students in International shows by the low ranking of Indonesian according TIMSS. Additionally, Indonesian set a textbook contains materials and exercise questions that students use as a tool in measuring the students' ability. But inevitable the textbook are not fully in accordance with the standards of TIMSS. This is because of the textbook in Indonesian are designed in accordance with the applicable curriculum. This study aims to analyze the suitability of the material and problem in mathematics in Tematik textbook of 2013 curriculum on fifth grades elementary student based on TIMSS taxonomy. The type of this study is content analysis with qualitative approach. The collecting data was conducted by documentation and interviews. In validity of data, researcher uses peer debriefing. The result of this study showed: 1) mathematics material to the content domain and mathematics problems to the cognitive domain in Tematik textbook not all fill the TIMSS proportion, 2) the material in Tematik textbook is dominated by numbers aspect is 55,88%, while shape and size of geometry is 33,82%, and data 10,30%. 3) The result of problems in Tematik textbook is dominated by applying aspect with the 45,93% percentage, while knowing aspect is 29,19%, and reasoning is 24,88%. This is showed that in Tematik textbook already contains questions to hone students' critical thinking skills.